Parental Anxiety with Emotional Development in Children - Sari, Penti Yunita; Aisyah, Siti (Mahesa Research Center, 2025)
This study examines the factors of emotional development in children through a literature review. The main focus is to evaluate what factors influence emotional development in children. The methodology used is a literature review from several relevant sources. Data retrieval using article search techniques through the Researchgate database, Google Scholar, and Google Search with the keywords used self-esteem. The data analysis technique used is a Systematic Literature Review. The findings show that emotional development in children is influenced by several factors, namely parental support factors, family environment, and parenting patterns. Emotional development in children will be optimal if they get support from their parents, a conducive family environment that supports every child's growth and development, and appropriate parenting patterns for children.